Implementation of a performance-based pre-school curriculum in a university setting De Mantecon - De Mantecon, Carmen Carceller 1936-
This study determines whether the implementation of the curriculum, teaching strategies, and classroom design activity has provided indicators of gains on the children's performance. Action research design was used in the process of curriculum implementation in an early childhood classroom setting.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Education, Preschool -- Curriculum; Academic achievement